Motivasi Keanggotaan Mahasiswa dalam Komunitas KMKS (Keluarga Mahasiswa Kudus Semarang): Studi pada Mahasiswa Perantau di UIN Walisongo Semarang - Ardaeta Nadia Rahmawati; Muhammad Fitahul Fikri; Dewi Ambarwati; Nurul Afifah (Asosiasi Riset Ilmu Kesehatan Indonesia, 2025)
This study explores the motivational factors that encourage students from Kudus who are studying at UIN Walisongo Semarang to join KMKS (Keluarga Mahasiswa Kudus Semarang), a regional student community that serves as a social and emotional support system for migrant students. Increased mobility in higher education often places migrant students in situations requiring significant academic, social, and cultural adjustment, making social support and a sense of belonging critical. Guided by McClelland’s theory of needs, this research aims to identify how the need for achievement, affiliation, and power is reflected in students’ experiences as members of KMKS. This study employs a qualitative phenomenological approach involving five participants selected through purposive sampling. Data were collected through semi-structured interviews and analyzed using thematic analysis. The findings reveal that students primarily join KMKS to fulfill strong affiliative needs, such as seeking social connectedness, emotional comfort, familiarity, and a supportive environment among peers from the same region. Additionally, participation in KMKS contributes to personal development, including increased confidence, improved communication skills, and readiness to take organizational responsibilities. The needs for achievement and power appear indirectly through involvement in committees, leadership roles, and contributions to organizational development. KMKS also functions as a crucial coping resource, helping students reduce stress, loneliness, and adaptation difficulties. The implications of this study highlight the importance of regional student communities as a meaningful support system for migrant students, emphasizing their role in facilitating adaptation, strengthening social identity, and fostering personal growth.